Simulation of complex formation of military equipment stocks in a combat zone using the component method - Oleg Fedorovych; Liudmyla Lutai; Yuliia Malieieva; Iaroslav Zamirets; Tetiana Pisklova (Авіаційно-космічна техніка та технологія, 2023)
The task of researching the multi-component composition of military equipment (tanks, artillery, aviation equipment, etc.) for supplying and forming the necessary stockpiles of weapons and their components in the military conflict zone to establish military parity of forces, is developed and solved. The research relevance is related to a comprehensive solution to the problem of forming the necessary stockpiles of weapons and their components in the combat zone, under the conditions of military threats. The purpose of this study is to use the component method to represent weapons and their components in the process of complex supply of military equipment to the combat zone for creating military parity of forces. The problems of the supply of weapons and their components in martial law conditions, which are associated with the complex multi-component structure of military equipment, the limited capabilities of manufacturers and suppliers of weapons, and the logistical risks of supply in conditions of military threats, are analyzed. A multi-layered component structure of military equipment is proposed for the systematic presentation of weapons and their components in the process of supply and formation of reserves in the combat zone. The logistics of the weapons and their component supply from army warehouses and military equipment from manufacturers’ warehouses are analyzed. The limited capabilities of manufacturers and suppliers of military equipment lead to the complication of the formation of necessary military equipment stockpiles in the military conflict zone, which can affect the nature of hostilities (transition from offensive to defensive actions). The lack of military equipment leads to the need to form defense orders for the creation and production of new types of weapons, including those with increased combat capability characteristics (range, accuracy, damage zone, etc.). Therefore, for the creation of new weapons or the modernization of existing models, it is proposed to use the multi-component architecture of a modern model of military equipment, considering the possible types of components (reusable, adaptive, new). An algorithm for the formation of a multi-component and multi-layered architecture of modern weapons using a precedent approach is proposed. For this, a precedent database is created, which is used to search for existing reusable components. Both quantitative and qualitative assessments of proximity are used in the process of searching in the database of precedents to assess the proximity of components. The model was created to optimize the logistic costs of supplying weapons and their components to the combat zone. The quantities of weapons and their components, the time of supply, and the risks of supply in conditions of military threats are used as supply indicators. The requirements for the supply of military equipment in the conditions of the risks of martial law are formed. The scientific novelty of the study is related to the component method use, which is used to form the logistics of the supply of weapons and their components to the military conflict zone, considering the limited capabilities of manufacturers and suppliers of military equipment in conditions of threats of martial law. The results of the study should be used to model the plans and logistics of supplying weapons and their components to the combat zone to create military parity of forces.